Analysis of Normal Values of Sagittal Spinopelvic Radiographic Parameters in Indian Population. Issue 1 (April 2016) - Sai Krishna, M. L. V.; Sharma, Deep; Menon, Jagdish
Introduction: Ever since Legaye et al. in 1998 first described the importance of pelvic incidence as an important determinant of sagittal spinal balance, several other radiographic spinopelvic parameters have been defined. There are an increasing number of reports and studies from around the world signifying the role of these parameters in the maintenance of global spinal balance. Alteration in the normal values of the spinopelvic parameters has been implicated in causing accelerated degeneration, low back pain and even sagittal plane deformities. The recent literature has suggested that the best functional outcomes after any spinal surgery were achieved when these parameters have been normalized. In this setting, it is extremely important to know the normal values of these parameters in the target population. Though these values have been well quantified in the Caucasian population, there is a dearth of information in other racial groups. A few studies done in other population groups have shown some ethnic differences in the normal values of these parameters. Thus in our study we aim to quantify the normal values of sagittal spinopelvic radiographic parameters in Indian population. Materials and Methods: The study was approved by our institute review board and the ethical committee. A total of 75 young, healthy and asymptomatic volunteers were enrolled into the study after taking a formal consent. There were 21 male and 54 female volunteers. Lateral sagittal digital radiographs of the whole spine including the base of skull up to the proximal ⅓ thigh were taken in standing position (patient is naturally standing up, looking horizontally, hands resting on a vertical support, upper limbs relaxed and elbows half bent). All the subjects were at a specific distance from the radiographic source and a single shot of X-rays have been used centering around D12. The parameters measured were pelvic incidence PI, pelvic tilt PT, sacral slope SS, thoracic kyphosis TK, lumbar lordosis LL, lordotic and kyphotic vertebra. All measurements were performed by two independent observers using the Surgimap spine software version 2.1.2. The values thus obtained were compared with the values described in other population groups. Results: The mean values obtained in our population group were PI-47.85, PT-13.03, SS-34.8, LL-54.68, TK-24.03. A significant correlation was found between SS-LL (r-0.817), PI-SS(R-0.813), PI-LL(r-0.692), PI-PT(r-0.589), LL-TK (r-0.505). Comparing our data with European data, the pelvic incidence of our study was lower. We also found that the values of spinopelvic parameters did not vary much between males and females except PT, which was found to have a statistically significant difference between sexes ( p = 0.019). Conclusion: The study demonstrated that pelvic incidence of the Asian population varied when compared with that of the Caucasian population. The pelvic incidence of our present study was similar to Japanese and Korean population. It was lower than that of the Caucasian population.